تأثير وسيلة القصّة المصورة في تعليم مهارة الكتابة لدى طلاب الفصل التاسع في مدرسة التربية الإسلامية جاندونج آغام - صيغيتا, فيبريمادونا; ريزال, إيكا; ياني, فجر; حسنة, نور (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
The researcher found the problems with little interest of the students of the ninth class in the Islamic Education School Canduang Agam on the skill of writing,especially in writing the Arabic sentence in the story, the illustrated story of stripe, and the teacher uses limited teaching methods in the writing skill. The purpose of the research is to find out the effect of the picture-story method on teaching the writing skill of ninth-grade students at the Islamic Education School, Canduang. The researcher used the experimental research to find the effect of the picture story method in teaching the writing skill. The research community is ninth class students at the Islamic Education School, Canduang. The researcher divided the sample into two classes: the experimental class and the control class. The sample was taken using the purposive sampling method and the research tools are observation and test. The researcher used a t-test to analyze the data. After analyzing the data using spss, the researcher obtained the results of the research: 1) the researcher found the T of the account 3,557 and the T of the table (df=n-2) 50=52-2, so the percentage value of the distribution of the Tof the table in the degree of 50 is 2,008. Based on this statement, it appeared that the t of account 3,557 is greater than the t of the table 2,008, and thus alternative hypothesis is accepted (Ha). 2) then researcher found the result (sig.2-tailed) 0,001, which is less than 0,05. Therefore, the alternative hypothesis is acceptable. The researcher takes the conclusion that these results are that use of the picture story method affects the teaching of writing skill among the students of the ninth class at the Islamic Education School, Canduang.